Electrosurgery and Temperature Increase in Tissue With a Passive Metal Implant - Martinsen, Tormod; Pettersen, Fred Johan; Kalvøy, Håvard; Tronstad, Christian; Kvarstein, Gunnvald; Bakken, Andre; Høgetveit, Jan Olav; Martinsen, Ørjan G.; Grimnes, Sverre; Frich, Lars (Frontiers in Surgery, 2019)
ABSTRACT Importance During monopolar electrosurgery in patients, current paths can be influenced by metal implants, which can cause unintentional tissue heating in proximity to implants. Guidelines concerning electrosurgery and active implants such as pacemakers or implantable cardioverter defibrillators have been published, but most describe interference between electrosurgery and the active implant rather than the risk of unintended tissue heating. Tissue heating in proximity to implants during electrosurgery may cause an increased risk of patient injury. Objective To determine the temperature of tissue close to metal implants during electrosurgery in an in-vitro model. Design, Setting, and Participants Thirty tissue samples (15 with a metal implant placed in center, 15 controls without implant) were placed in an in vitro measurement chamber. Electrosurgery was applied at 5–60 W with the active electrode at three defined distances from the implant while temperatures at four defined distances from the implant were measured using fiber-optic sensors. Main Outcomes and Measures Tissue temperature increase at the four tissue sites was determined for all power levels and each of the electrode-to-implant distances. Based on a linear mixed effects model analysis, the primary outcomes were the difference in temperature increase between implant and control tissue, and the estimated temperature increase per watt per minute. Results Tissues with an implant had higher temperature increases than controls at all power levels after 1 minute of applied electrosurgery (mean difference of 0.16°C at 5W, 0.50°C at 15W, 1.11°C at 30W and 2.22°C at 60W, all with p<0.001). Temperature increase close to the implant was estimated to be 0.088°C/W/min (95% CI: 0.078–0.099°C/W/min; p<0.001). Temperature could increase to above 43°C after 1 minute of 60 W. Active electrode position had no significant effect on temperature increases for tissues with implant (p=0.6). Conclusions and Relevance The temperature of tissue close to a metal implant increases with passing electrosurgery current. There is a significant risk of high tissue temperature when long activation times or high power levels are used.